(untitled) (Bangladesh Journal of Public Administration, 2021)
Engaging citizens through a community-based organisation is not a newphenomenon. Research around the world has shown that citizenengagement is one of the most significant ways of combating corruption and promoting good governance. Transparency International Bangladesh (TIB) is undertaking similar types of activities through the Committee of Concerned Citizens (CCCs) and Youth Engagement and Support (YES) Groups. The question is, how much difference is it making in society vis-à-vis preventing corruption? Considering TIB as a case study drawing in-depth interviews, participation observation and document analysis, this paper has found that both CCCs and YES activities are dominated by coercive and mimetic isomorphism to prevent corruption. Second, TIB has managed to create awareness through engaging citizens, the whole process as a ‘tortoise movement.’ This suggests that the movement against the corruption of these groups is prolonged and time-consuming, and more importantly, it does not make ‘direct impact’ on service delivery. Third, it also suggests that donor-driven ‘isomorphic’ approach may prove to be less effective, considering the societal context of Bangladesh. Finally, this paper also identified some loopholes that are mainly linked with the ‘tortoise movement.